PERAN USAHA PEREMPUAN DALAM AKTIVITAS BUDIDAYA RUMPUT LAUT UNTUK MENINGKATKAN PEREKONOMIAN KELUARGA DITINJAU DALAM PRESPEKTIF EKONOMI ISLAM DI KABUPATEN TAKALAR - Suarni, Agusdiwana; Wahyuni, Yuyun (Universitas Muhammadiyah Makassar, 2020)
This study to determine the role of women business in seaweed cultivication activities to improve the family economic and how Islamic economics persp[ective in role of women business in seaweed cultivication activities. The concept of thinking so far is that women only responsible for domestic matters, but more than that women has proved to give the contribute greatly to economic survival and prosperty of household and society. The method in this research is qualitative descriptive. Date sources used were primary and secondary . data collection used observation, interview, and documentation. To analyze the data researchers used qualitative descriptive method. The results obtained from this study were that women play an very important role in seaweed cultivication activities, in fact almost all vocation is carried out by women such as binding,releasing, and drying. From some of income obtained by informants, the lowest is Rp. 1.000,000 / month and the highest is Rp. 3,500,000 / month. Women may worked inside or outside of house, autonomous or with others, provided that work had done is halal and does not infringe in Islamic terms, then in Islamic Ekonomic perspective is permitted.Keywords: Women, Cultivication Seaweed, Islamic Economic Perspective.